Recent advances in oral contraceptive pills: a review of evolving formulations and innovations - Rajopadhye, Bhagyashri; Dhakne, Aishwarya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Recent innovations in oral contraceptive pills (OCPs) focus on reducing adverse effects and enhancing user control. Key advancements include low-dose/extended-cycle formulations, customization for conditions like polycystic ovary syndrome (PCOS), and improved safety profiles. User-centric features like over-the-counter (OTC) availability (Opill), smart packaging, and digital health integration further improve accessibility and adherence. Since the FDA approved Enovid in 1960, OCP development has continued to evolve. Modifications such as lower doses and extended cycles aim to minimize side effects (e.g., cardiovascular and metabolic) while maintaining efficacy. Customization addresses specific health conditions, improving patient suitability. This review aims to highlight how these developments improve efficacy, reduce side effects, and enhance convenience. This review also outlines key advancements in OCPs, associated explicitly with innovations in formulation, safety, and user-friendliness. For this purpose, this review synthesizes developments in OCP technology and delivery, based on established scientific literature and regulatory milestones. It examines formulation changes, safety enhancements, and user-focused innovations with key examples, including Opill's OTC approval and digital health tools. Thus, this review concludes that innovations in OCPs, spanning formulations, safety, and user experience, offer significant benefits that feature customization, OTC access, and digital integration, empowering women and improving adherence. These advancements also promise a more effective, accessible, and user-controlled contraceptive future.